Schistosoma mansoni Infection Is Associated With a Higher Probability of Tuberculosis Disease in HIV-Infected Adults in Kenya. (1st February 2021) - McLaughlin, Taryn A.; Nizam, Azhar; Hayara, Felix Odhiambo; Ouma, Gregory Sadat; Campbell, Angela; Khayumbi, Jeremiah; Ongalo, Joshua; Ouma, Samuel Gurrion; Shah, N. Sarita; Altman, John D.; Kaushal, Deepak; Rengarajan, Jyothi; et al.
Abstract : Background: Helminth infections can modulate immunity to Mycobacterium tuberculosis (Mtb). However, the effect of helminths, including Schistosoma mansoni (SM), on Mtb infection outcomes is less clear. Furthermore, HIV is a known risk factor for tuberculosis (TB) disease and has been implicated in SM pathogenesis. Therefore, it is important to evaluate whether HIV modifies the association between SM and Mtb infection. Setting: HIV-infected and HIV-uninfected adults were enrolled in Kisumu County, Kenya, between 2014 and 2017 and categorized into 3 groups based on Mtb infection status: Mtb-uninfected healthy controls, latent TB infection (LTBI), and active TB disease. Participants were subsequently evaluated for infection with SM. Methods: We used targeted minimum loss estimation and super learning to estimate a covariate-adjusted association between SM and Mtb infection outcomes, defined as the probability of being Mtb-uninfected healthy controls, LTBI, or TB. HIV status was evaluated as an effect modifier of this association. Results: SM was not associated with differences in baseline demographic or clinical features of participants in this study, nor with additional parasitic infections. Covariate-adjusted analyses indicated that infection with SM was associated with a 4% higher estimated proportion of active TB cases in HIV-uninfected individuals and a 14% higher estimated proportion of active TB cases in HIV-infected individuals. There were no differences in estimated proportions of LTBI cases. Conclusions: We provide evidence that SM infection is associated with a higher probability of active TB disease, particularly in HIV-infected individuals. Abstract : Supplemental Digital Content is Available in the Text.